Development of Digital Competences in Students of a Public State-Owned Chilean University Considering the Safety Area - Silva-Quiroz, J (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The present study was carried out in a Chilean public university with the purpose of describing digital competences in safety area and their relationship with contextual variables in first-year students of different programs. In this research study, we processed the competences of the safety area of the COMPDIG-PED test, which is based on the European reference framework for digital skills DIGCOMP. The instrument was applied to 4360 higher education students, attending undergraduate courses in 2021 and 2022. The results indicated a relationship between the context variables analyzed through the COMPDIG-PED test and the digital safety competences. This relationship is linked to higher scores in the female gender, in students with more years of experience in the use of digital technologies, in those who came from private paid or subsidized institutions, and in those who were trained in a humanist scientific education. © 2023 by the authors.